Effect of Genetic Modification on Plant Reproductive System - Zuhrotul Ummah; Laili Nur Istiqomah; Siti Mahmudah (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2023)
Genetic modification is a technique used to change the genetic traits of an organism by inserting genes from other organisms. The aim of this research is to examine the effect of genetic modification on the plant reproductive system. In This research uses the literature study method by collecting and analyzing data from various scientific sources. From various scientific sources. The results of this study show that genetic modification can affect the plant reproductive system such as increase in crop yields, resistance to pests and diseases, and adaptation to the changing environment. Plants to a changing environment. This research underscores the importance of an in-depth understanding of the effects of genetic modification on plant reproductive systems as part of efforts to manage the reproductive system as part of the effort to manage and utilize this technology wisely and sustainably for the sake of the environment. This technology wisely and sustainably for the sustainability of agriculture and global ecosystems.